2016
DOI: 10.3201/eid2207.151377
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Spectrum Cephalosporin-ResistantSalmonella entericaserovar Heidelberg Strains, the Netherlands1

Abstract: Extended-spectrum cephalosporin-resistant Salmonella enterica serovar Heidelberg strains (JF6X01.0022/XbaI.0251, JF6X01.0326/XbaI.1966, JF6X01.0258/XbaI.1968, and JF6X01.0045/XbaI.1970) have been identified in the United States with pulsed-field gel electrophoresis. Our examination of isolates showed introduction of these strains in the Netherlands and highlight the need for active surveillance and intervention strategies by public health organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 13 publications
(11 reference statements)
3
65
0
Order By: Relevance
“…The most frequently-isolated bla CMY−2 carrying plasmids of S. Heidelberg isolates include IncI1 (e.g. subtyping ST12 and ST25) and IncA/C (ST2), which have likely contributed to the widespread distribution of CSH and other 3GC-resistant NTS serovars from human and animal sources [58, 8385]. …”
Section: Results (Headings As Per the Codex Guidelines)mentioning
confidence: 99%
“…The most frequently-isolated bla CMY−2 carrying plasmids of S. Heidelberg isolates include IncI1 (e.g. subtyping ST12 and ST25) and IncA/C (ST2), which have likely contributed to the widespread distribution of CSH and other 3GC-resistant NTS serovars from human and animal sources [58, 8385]. …”
Section: Results (Headings As Per the Codex Guidelines)mentioning
confidence: 99%
“…Quinolones were used frequently in treatment regimens and also as a feed additives in poultry industry [24] . In recent years several studies have been reported about third-generation cephalosporin resistance patterns of Salmonella was isolated from domestic animals and human [25][26][27] . In parallel with this situation, Kameyama et al emphasized that 3rd-generation cephalosporin-resistant S. Infantis associated with β-lactamases is increasing in worldwide [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Presumptive extended-spectrum-cephalosporinase-producing isolates were identified using matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (Brucker, Coventry, United Kingdom), while Salmonella isolates were further serotyped by the microtitration method. Antibiotic susceptibility of the isolates was assessed by broth microdilution and interpreted according the epidemiologic cutoff values recommended by the European Committee on Antimicrobial Susceptibility Testing (http://mic .eucast.org), whereas ESBL and/or AmpC production was evaluated by a combined disc test, as previously described (9).…”
mentioning
confidence: 99%
“…Genes conferring the ESC r phenotype were sought and their genetic location on either the chromosome or a plasmid was determined as previously described (9). Standard methods (PCRbased replicon [rep] typing, plasmid multilocus sequence typing [pMLST]/plasmid double-locus sequence typing [pDLST]/replicon sequence typing [RST], and S1 nuclease pulsed-field gel electrophoresis [PFGE]) were applied for further plasmid analysis, while the conjugal transferability of the extended-spectrum cephalosporinase genes and the presence of known insertion sequences (ISs) upstream of them were examined (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation